Análise paramétrica de antenas de linha dobrada de microfita (microstrip meander line antennas - mmla) - Freitas, Eudes Fernandes de (2019)
This work presents a parametric study performed microstrip meander line antennas, where there was modification in their physical parameters of the shape of the radiating element of the antenna and the ground plane. A total of eighteen MMLA configurations were studied, ten of which were also constructed. The results were obtained and compared by computer simulation and measurements with the aid of a vector network analyzer, validating the computer simulations. The antennas showed a multiband behavior, narrow bandwidth and different radiation diagrams for each variation in the ground plane. The variations also had a significant influence on the maximum gain presented by the antennas. Modifications made to the radiating element of the antennas also caused changes in antenna gain as well as in resonance frequencies compared to each other